2018
DOI: 10.1038/s41422-018-0120-9
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination of Rheb governs growth factor-induced mTORC1 activation

Abstract: Mechanistic target of rapamycin mTOR complex 1 (mTORC1) plays a key role in the integration of various environmental signals to regulate cell growth and metabolism. mTORC1 is recruited to the lysosome where it is activated by its interaction with GTP-bound Rheb GTPase. However, the regulatory mechanism of Rheb activity remains largely unknown. Here, we show that ubiquitination governs the nucleotide-bound status of Rheb. Lysosome-anchored E3 ligase RNF152 catalyzes Rheb ubiquitination and promotes its binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 59 publications
5
82
0
Order By: Relevance
“…The results showed that serum‐starved MEF cells treated with lactate disrupted the TSC2 and Rheb interaction in a dose‐dependent manner (Fig EV3D), which is consistent with the dose‐dependent effects of lactate on mTORC1 activation (Fig EV2F). The level of the Rheb‐GTP response to growth factor withdrawal and insulin stimulation and the interaction of TSC2 with Rheb under serum‐starved conditions are consistent with previous findings (Fig EV3E and F). We further confirmed that 20 mM lactate disrupted the TSC2 and Rheb interaction in serum‐starved HCT116 cells (Figs C and EV3G).…”
Section: Resultssupporting
confidence: 92%
“…The results showed that serum‐starved MEF cells treated with lactate disrupted the TSC2 and Rheb interaction in a dose‐dependent manner (Fig EV3D), which is consistent with the dose‐dependent effects of lactate on mTORC1 activation (Fig EV2F). The level of the Rheb‐GTP response to growth factor withdrawal and insulin stimulation and the interaction of TSC2 with Rheb under serum‐starved conditions are consistent with previous findings (Fig EV3E and F). We further confirmed that 20 mM lactate disrupted the TSC2 and Rheb interaction in serum‐starved HCT116 cells (Figs C and EV3G).…”
Section: Resultssupporting
confidence: 92%
“…2a). 150 Ubiquitination in the adenylate-activated protein kinase signaling pathway Adenylate-activated protein kinase (AMPK), the master sensor of energy in cells and organisms, is the core in regulating intracellular metabolic homeostasis, and its mutation is associated with tumorigenesis. 151,152 When the cellular level of ATP decreases and AMP/ATP increases, the activation of AMPK increases.…”
Section: Ubiquitination In Tumor Metabolism Regulationmentioning
confidence: 99%
“…The results showed that expression of most of the genes was not affected by the presence or absence of Shh (Figure 4A). However, RNF152 , which encodes an E3 ubiquitin ligase (Deng et al, 2019; Deng et al, 2015), was strongly induced in Shh H explants with a weaker induction with Shh L , suggesting that RNF152 was expressed preferentially in the FP.…”
Section: Resultsmentioning
confidence: 99%
“…The RNF152 gene encodes an E3 ubiquitin ligase targeting the small GTPase RagA (Deng et al, 2019; Deng et al, 2015; Kim et al, 2008), and the GTP-bound active form of RagA positively regulates the mTOR signalling pathway (Efeyan et al, 2014; Shaw, 2008). Actually the expression of the dominant-negative RagA (DN-RagA) blocks cell proliferation in the electroporated cells while the constitutively-active RagA (CA-RagA) activates it, without changing the FP cell fate (Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation